IMPLEMENTASI GAYA KEPEMIMPINAN DEMOKRATIS DAN BUDAYA ORGANISASI DALAM MENINGKATKAN KINERJA PEGAWAI PADA KANTOR KEMENTERIAN AGAMA KOTA BATU - Lathifa, Muthia (Program Studi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2025)
There are several factors that can affect employee performance, one of which is leadership style and organizational culture. The leadership style of the Head of the Batu City Ministry of Religious Affairs is a democratic leadership style. This leadership style has an important role in creating a conducive and participatory work atmosphere to achieve organizational effectiveness in improving employee performance. Then a strong organizational culture will provide a clear foundation for behavior, values, and norms that must be followed by all members of the organization. This can influence the attitudes and behavior of all components of the organization, thus creating a conducive work environment to achieve optimal performance. This study uses a descriptive qualitative approach with a case study research type. The research data were obtained from interviews, observations and documentation, and analyzed by data condensation, data presentation and drawing conclusions. The results of this study are: 1) The implementation of the democratic leadership style of the Head of the Batu City Ministry of Religious Affairs can be seen from his attitude which is in accordance with the indicators of a democratic leadership style, such as opinions focused on the results of deliberations, tolerance, providing opportunities for employees to develop careers, open to criticism, building a family atmosphere, knowing the strengths and weaknesses of employees, communicating well with employees, and being responsive to situations. 2) The implementation of organizational culture in the Batu City Ministry of Religious Affairs Office shows a positive organizational culture. This can be seen from the implementation of organizational culture indicators consisting of: a) Norms consisting of religious norms, law, politeness and morality. b) Dominant values ​​in the form of the application of the core value of BerAKHLAK, 5 values ​​of the Ministry of Religious Affairs work culture, the value of Faith and Piety, the value of my work is my worship and the value of mutual cooperation. c) The rules that apply in the Batu City Ministry of Religious Affairs Office are all rules or policies that have been regulated by the state. d) The organizational climate of the Batu City Ministry of Religious Affairs shows a cool and harmonious working atmosphere. Employees always implement togetherness and mutual cooperation and help each other. This small work environment also causes work to pile up in several employees.